Use of ChAd3-EBO-Z Ebola virus vaccine in Malian and US adults, and boosting of Malian adults with MVA-BN-Filo: a phase 1, single-blind, randomised trial, a phase 1b, open-label and double-blind, dose-escalation trial, and a nested, randomised, double-blind, placebo-controlled trial. Issue 1 (January 2016) - Tapia, Milagritos D; Sow, Samba O; Lyke, Kirsten E; Haidara, Fadima Cheick; Diallo, Fatoumata; Doumbia, Moussa; Traore, Awa; Coulibaly, Flanon; Kodio, Mamoudou; Onwuchekwa, Uma; Sztein, Marcelo B; Wahid, Rezwanul; et al.
Summary: Background: The 2014 west African Zaire Ebola virus epidemic prompted worldwide partners to accelerate clinical development of replication-defective chimpanzee adenovirus 3 vector vaccine expressing Zaire Ebola virus glycoprotein (ChAd3-EBO-Z). We aimed to investigate the safety, tolerability, and immunogenicity of ChAd3-EBO-Z in Malian and US adults, and assess the effect of boosting of Malians with modified vaccinia Ankara expressing Zaire Ebola virus glycoprotein and other filovirus antigens (MVA-BN-Filo). Methods: In the phase 1, single-blind, randomised trial of ChAd3-EBO-Z in the USA, we recruited adults aged 18–65 years from the University of Maryland medical community and the Baltimore community. In the phase 1b, open-label and double-blind, dose-escalation trial of ChAd3-EBO-Z in Mali, we recruited adults 18–50 years of age from six hospitals and health centres in Bamako (Mali), some of whom were also eligible for a nested, randomised, double-blind, placebo-controlled trial of MVA-BN-Filo. For randomised segments of the Malian trial and for the US trial, we randomly allocated participants (1:1; block size of six [Malian] or four [US]; ARB produced computer-generated randomisation lists; clinical staff did randomisation) to different single doses of intramuscular immunisation with ChAd3-EBO-Z: Malians received 1 × 10 10 viral particle units (pu), 2·5 × 10 10 pu, 5 × 10 10 pu, or 1 × 10 11 pu; US participants received 1 × 10 10 pu or 1 × 10 11 pu. We randomly allocated Malians in the nested trial (1:1) to receive a single dose of 2 × 10 8 plaque-forming units of MVA-BN-Filo or saline placebo. In the double-blind segments of the Malian trial, investigators, clinical staff, participants, and immunology laboratory staff were masked, but the study pharmacist (MK), vaccine administrator, and study statistician (ARB) were unmasked. In the US trial, investigators were not masked, but participants were. Analyses were per protocol. The primary outcome was safety, measured with occurrence of adverse events for 7 days after vaccination. Both trials are registered withClinicalTrials.gov, numbersNCT02231866 (US) andNCT02267109 (Malian). Findings: Between Oct 8, 2014, and Feb 16, 2015, we randomly allocated 91 participants in Mali (ten [11%] to 1 × 10 10 pu, 35 [38%] to 2·5 × 10 10 pu, 35 [38%] to 5 × 10 10 pu, and 11 [12%] to 1 × 10 11 pu) and 20 in the USA (ten [50%] to 1 × 10 10 pu and ten [50%] to 1 × 10 11 pu), and boosted 52 Malians with MVA-BN-Filo (27 [52%]) or saline (25 [48%]). We identified no safety concerns with either vaccine: seven (8%) of 91 participants in Mali (five [5%] received 5 × 10 10 and two [2%] received 1 × 10 11 pu) and four (20%) of 20 in the USA (all received 1 × 10 11 pu) given ChAd3-EBO-Z had fever lasting for less than 24 h, and 15 (56%) of 27 Malians boosted with MVA-BN-Filo had injection-site pain or tenderness. Interpretation: 1 × 10 11 pu single-dose ChAd3-EBO-Z could suffice for phase 3 efficacy trials of ring-vaccination containment needing short-term, high-level protection to interrupt transmission. MVA-BN-Filo boosting, although a complex regimen, could confer long-lived protection if needed (eg, for health-care workers). Funding: Wellcome Trust, Medical Research Council UK, Department for International Development UK, National Cancer Institute, Frederick National Laboratory for Cancer Research, Federal Funds from National Institute of Allergy and Infectious Diseases.